Surfactant-doped reverse-mode polymer-dispersed liquid crystal display with enhanced properties. Issue 2 (26th January 2016) - Ahmad, Farzana; Jamil, Muhammad; Lee, Jin Woo; Jang, Gwon Neung; Jeon, Young Jae
ABSTRACT: In this article, a nonionic surfactant Brij30 has been used to vertical align the negative anisotropic liquid crystal. The surfactant is further used in reverse-mode polymer-dispersed liquid crystal display to enhance the electro-optical properties. This work shows an enhancement of contrast ratio simply with the addition of surfactant. In addition, contact angle and surface free energies have been determined to judge the role of surfactant in control of surface orientation of liquid crystal molecules. GRAPHICAL ABSTRACT: